2002
DOI: 10.1073/pnas.242625499
|View full text |Cite
|
Sign up to set email alerts
|

The spatial receptive field of thalamic inputs to single cortical simple cells revealed by the interaction of visual and electrical stimulation

Abstract: Electrical stimulation of the thalamus has been widely used to test for the existence of monosynaptic input to cortical neurons, typically with stimulation currents that evoke cortical spikes with high probability. We stimulated the lateral geniculate nucleus (LGN) of the thalamus and recorded monosynaptically evoked spikes from layer 4 neurons in visual cortex. We found that with moderate currents, cortical spikes were evoked with low to moderate probability and their occurrence was modulated by ongoing senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 26 publications
(32 reference statements)
9
86
0
Order By: Relevance
“…Stimulation of the neocortex revealed the presence of strong inhibition, thus preventing the propagation of electrically induced activation over multi-synaptic pathways. Th is is in good agreement with the prominence of inhibition both in its duration 10,53 and in the presence of a wealth of diff erent inhibitory interneurons in the neocortex 54 . Comparable inhibitory mechanisms do not seem to matter in the case of stimulation of the cerebellar output.…”
Section: Discussionsupporting
confidence: 75%
“…Stimulation of the neocortex revealed the presence of strong inhibition, thus preventing the propagation of electrically induced activation over multi-synaptic pathways. Th is is in good agreement with the prominence of inhibition both in its duration 10,53 and in the presence of a wealth of diff erent inhibitory interneurons in the neocortex 54 . Comparable inhibitory mechanisms do not seem to matter in the case of stimulation of the cerebellar output.…”
Section: Discussionsupporting
confidence: 75%
“…Thalamocortical synapses are more effective than intracortical synapses 94 , but they form only a small fraction of the synapses onto SSCs 95,96 . Nevertheless, collectively they seem to be efficient in driving the SSCs 45,97 . The reason for this efficiency was elucidated in another cortical area, in neurons that project from the ventroposteromedial thalamus (VPM) to the barrel cortex 98 and that respond to whisker movement.…”
Section: Gated Temporal Information Transfer Between Cortical Layer 4mentioning
confidence: 97%
“…Neurons in layer 4 of the primary visual cortex can also fire with high precision in response to visual inputs 45,46 . Neurons in the mediotemporal cortex in turn receive inputs from the primary visual cortex and respond to motion.…”
Section: Evidence For Spike-time Precision In the Visual Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas field potential recordings suggest substantial geniculocortical depression in the rat (Jia et al, 2004), extracellular studies in the cat found facilitation of spike efficacy in response to LGN spikes elicited at short intervals (Usrey et al, 2000). Additionally, responses to electrical stimulation of the LGN are facilitated during and after the presentation of a visual stimulus (Kara et al, 2002).…”
Section: Introductionmentioning
confidence: 98%